Emerging Paradoxes Encountered by Organizations Regarding Self-Initiated Expatriates in the USA - Yussuf, Osman (Current Progress in Arts and Social Studies Research Vol. 7, 2024)
Expatriates expressed appreciation for organizational policies that facilitated integration, such as the implementation of cross-cultural training initiatives and the establishment of mentorship programs Nevertheless, certain individuals observed that these habits may unintentionally impede their independence by compelling them to conform. The prevalence of self-initiated expatriates (SIEs) has increased as a result of the expanding global nature of commercial activities. The current corpus of scholarly literature has extensively explored various aspects of expatriation. However, there is a limited understanding of the conflicting challenges that organizations confront while managing SIEs within the framework of the United States. The primary aim of this study is to provide a comprehensive understanding of the inherent inconsistencies that arise in organizations while managing Socially and Environmentally Responsible Initiatives within the United States. The present study utilizes a qualitative research approach, employing semi-structured interviews and theme analysis to investigate the experiences of establishments grappling with the paradoxes linked to SIE. The Paradox theory and the Theory of Behavior are adopted for this study because the use of both the Paradox Theory and the Theory of Behavior in one’s research on self-initiated expatriates’ management of the integration autonomy paradox can offer a full theoretical framework for comprehending the intricacies of their experiences. The focus of this study encompasses a wide range of industries and organizational scales that are now existent within the United States. As a result, its inclusion enhances the potential applicability and generalizability of the findings. Based on the analysis conducted, it can be deduced that organizations face certain contradictory issues when they interact with social impact enterprises. The matter of achieving a balance between organizational control and individual autonomy comes as a result of the comparatively higher levels of self-direction and independence commonly demonstrated by self-employed individuals. The paradoxical position described above presents a challenge for organizations seeking to strike a balance between maintaining control over their worldwide operations and capitalizing on the unique skills and perspectives that SIEs provide. The current research study provides an academic addition to the field of expatriation and paradox theory by shedding light on the unique paradoxes faced by organizations that oversee SIEs in the United States. The anticipated outcomes of this study are anticipated to yield practical ramifications for the domain of human resource management and organizational development. This research concludes that the integration-autonomy issue is a fluid process of negotiation and adaptation. By embracing the inherent complexity, firms can harness self-initiated expats’ unique skills and ability to link diverse cultural ideas to deliver fresh solutions. The conclusions of this research affect expatriate assignment management, cross-cultural diversity, and organizational effectiveness. The study is expected to provide significant insights for organizations aiming to efficiently manage and harness the potential of SIEs.